The relationship among gender, students’ habit in online reading and vocabulary mastery - Aqidatul Izzah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Reading is important in any field and degree of education as the basic skill to obtain information. Developing reading as a habit allows the reader to become more intelligent as practicing reading improves analytical skill in comprehending text. In terms of EFL, reading also have potential to develop vocabulary. Reading is habitual activities that determined by individual characteristics such as gender. Therefore, the researcher aims to study reading habit and vocabulary mastery from male and female students. This research is conducted using quantitative correlational research to answer the research question. The participants in this study consist of 115 students, 31 male and 84 female students from the 3rd semester in English language department at the University of Islam Malang. The instrument used in this study is in the form of reading habit questionnaire and vocabulary mastery test. The data analyzed using independent sample t test using SPSS 24.0 to measure the significant difference between male and female students in reading habit and vocabulary mastery. The result indicated that there is no significant difference between male and female students in terms of reading habit and vocabulary mastery. Moreover, the score between male and female students are not significantly different. Therefore, it can be concluded that there is significant correlation between students vocabulary mastery and reading habit but there is no significant correlation between gender with vocabulary mastery and reading habit.Key Words: Reading habit, Gender, Vocabulary Mastery.